2011
DOI: 10.1108/17506221111145968
|View full text |Cite
|
Sign up to set email alerts
|

Compact fluorescent lamps and electricity consumption trend in residential buildings in Ilorin, Nigeria

Abstract: PurposeThe purpose of this study is to examine the electricity consumption trend in residential buildings using incandescent lamps and retrofitting with compact fluorescent lamps (CFLs).Design/methodology/approachQuestionnaires were administered to capture the necessary data from three randomly selected residential estates in Ilorin, Nigeria. In total, 8,840 sampled incandescent lamps were retrofitted with CFLs. The electric energy in kilowatt hour (kWh) consumed prior to replacement for three months was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…Similarly, test results carried out on percentage energy savings in ODLT lecture hall also revealed that there were significant differences between the energy consumption before and after installations of CFLs and LED lamps. Moreover, about 47% reduction in electricity consumption were achieved using compact fluorescent lamps, which is also in line with research carried out by [28] and 73% for light emitting diode fittings. Also, the test results carried out on percentage energy savings for Moremi halls also revealed that there were significant differences between the energy consumption before and after installations of CFLs and LED.…”
Section: Percentage Energy Savings For Compact Fluorescent Lamps and Light Emitting Diode Lampssupporting
confidence: 86%
“…Similarly, test results carried out on percentage energy savings in ODLT lecture hall also revealed that there were significant differences between the energy consumption before and after installations of CFLs and LED lamps. Moreover, about 47% reduction in electricity consumption were achieved using compact fluorescent lamps, which is also in line with research carried out by [28] and 73% for light emitting diode fittings. Also, the test results carried out on percentage energy savings for Moremi halls also revealed that there were significant differences between the energy consumption before and after installations of CFLs and LED.…”
Section: Percentage Energy Savings For Compact Fluorescent Lamps and Light Emitting Diode Lampssupporting
confidence: 86%
“…However, the results found that higher education had a negative impact on households' likelihood of switching to electricity. This is however not surprising given that most parts of Maiduguri have been cut off from electricity supply due to destruction of the power lines by Boko Haram insurgents and even where it is available, the supply is poor and very erratic that it is seldom used as a primary energy source for cooking by most households [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Energising this sector has been a challenge for the country given the energy-intensive nature of the manufacturing procedures of MSMEs (Naik and Bagodi, 2021). Aside from the residential sector, MSMEs are the major electricity consumers in Nigeria (Sule et al , 2011; Nwokoye et al , 2017). In comparison to large enterprises, MSMEs are less energy-efficient with worrying implications for energy availability and environmental sustainability (Maheshwari et al , 2021; Naik and Bagodi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Energising this sector has been a challenge for the country given the energy-intensive nature of the manufacturing procedures of MSMEs (Naik and Bagodi, 2021). Aside from the residential sector, MSMEs are the major electricity consumers in Nigeria (Sule et al, 2011;Nwokoye et al, 2017). In comparison to…”
Section: Introductionmentioning
confidence: 99%